Acrylate/Nanofibrillated Cellulose Nanocomposites and Their Use for Paper Coating. (24th December 2018) - Hassan, Mohammad L.; Fadel, Shaimaa M.; Hassan, Enas A.
Abstract : Nanofibrillated cellulose (NFC) isolated from TEMPO-oxidized rice straw was used to improve thermal and tensile strength properties of acrylate polymer films. Acrylate/NFC mixture containing 15% NFC was used for paper coating, and properties of paper sheets including tensile strength, water absorption, and microscopic structure were investigated. The results showed that the presence of NFC in the acrylate matrix significantly improved tensile strength properties and thermomechanical properties of the acrylate polymer and caused moderate increase in its moisture sorption. The presence of NFC in acrylate emulsion caused significant increase in its viscosity. Paper sheets coated with different thin layers (from 0.2 to 6 microns) of acrylate/NFC showed improvement in tensile strength and decrease of water absorption.